Creation of Contemporary Batik with Brush Stroke Motifs Using Layering Technique - Sekar Fardhani, Ahda Yunia; Katresna, Alaika Sugih (Mudra Jurnal Seni Budaya, 2024)
One of Indonesia's growing creative sectors is the Batik industry. The development of the batik industry not only benefits artisans or small and medium-sized enterprises (SMEs) but serves as a creative industry supporting the national economy. This has prompted the government to implement policies to ensure the growth of the batik industry, including promoting innovation and creativity. The author sees opportunities to create contemporary batik in line with these government policies. The term "contemporary" is defined as modern and current. Contemporary batik is characterized by motifs and styles that are not bound by specific rules, making it tailored to consumer preferences. One example of contemporary batik creation, the basis for this research, is brushstroke batik. Brushstroke batik refers to batik motifs created using a brush to apply wax during the batik process, resulting in distinctive patterns. Based on the researcher's observations at a brushstroke batik production house, the coloring process involves basic techniques such as dipping and brushing. However, there is a trend towards using a variety of colors in one batik design. The research identifies the potential to develop designs by focusing on the composition of brushstroke motifs as the main element and exploring various color combinations. This development aims to give novelty in the scientific realm of contemporary textile design, especially in batik innovation towards a modern direction. The development will be carried out using visual composition and coloring layering techniques. This research employs a qualitative method, utilizing literature review, observation, characteristic study, and experimentation for data collection.